What predicts suicidality among psychologists? An examination of risk and resilience. Issue 2 (7th February 2023) - Zuckerman, Stephanie; Lightsey, Owen Richard; White, Joseph Michael
Abstract: Psychologists may have a uniquely high risk for suicide. We examined whether, among 172 psychologists, factors predicting suicide risk among the general population (e.g., gender and mental illness), occupational factors (e.g., burnout and secondary traumatic stress), and past trauma predicted suicidality. We also tested whether resilience and meaning in life were negatively related to suicidality and whether resilience buffered relationships between risk factors and suicidality. Family history of mental illness, number of traumas, and lifetime depression/anxiety predicted higher suicidality, whereas resilience predicted lower suicidality. At higher levels of resilience, the relationship between family history of suicide and suicidality was stronger.